Hunger games. 2, Catching fire - Collins, Suzanne (New York, New York : Scholastic Inc., 2013)
"By winning the annual Hunger Games, District 12 tributes Katniss Everdeen and Peeta Mellark have secured a life of safety and plenty for themselves and their families, but because they won by defying the rules, they unwittingly become the faces of an impending rebellion"
"This book was originally published in hardcover by Scholastic Press in 2009"--Verso de la page de titre.
Part of The Hunger Games Trilogy boxset.
Keywords: Insurgency -- Juvenile fiction; Survival -- Juvenile fiction; Television programs -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Contests -- Juvenile fiction; Dystopias -- Juvenile fiction; Girls -- Juvenile fiction; Courage -- Juvenile fiction; Adventure and adventurers; Young adult fiction; Fiction; Juvenile works; Science fiction; Young adult works; Science fiction; Science fiction